Remote PEERS® for preschoolers: A pilot parent-mediated social skills intervention for young children with social challenges over telehealth - Factor, Reina S.; Glass, Leila; Baertschi, Daliah; Laugeson, Elizabeth A. (Frontiers in Psychiatry, 2022)
Social differences characteristic of autism spectrum disorder (ASD) and other developmental disabilities are evident in early childhood and are associated with later difficulties. Unfortunately, there is a paucity of evidence-based interventions explicitly targeting social skills development for young children, few actively integrate parents and caregivers, and even fewer have remote models. The importance of providing accessible, tailored services for families in the wake of the COVID-19 pandemic, prompted the creation of a parent-mediated telehealth version of PEERS® for Preschoolers (P4P), a pre-existing, evidence-based social skills intervention for children 4-6 years focused on making and keeping friends. This methodological paper documents the implementation, feasibility, and satisfaction of a novel telehealth group-based delivery of P4P. Qualitative results indicate acceptable feasibility and satisfaction. Additionally, following completion there was an increase in parental confidence in social coaching and increased use of child social skills. Future work will evaluate quantitative outcomes and comparisons between delivery methods (e.g., telehealth vs. in-person).